2021
DOI: 10.3389/fphar.2020.572637
|View full text |Cite
|
Sign up to set email alerts
|

Kanglexin protects against cardiac fibrosis and dysfunction in mice by TGF-β1/ERK1/2 noncanonical pathway

Abstract: Cardiac fibrosis is a common pathological manifestation accompanied by various heart diseases, and antifibrotic therapy is an effective strategy to prevent diverse pathological processes of the cardiovascular system. We currently report the pharmacological evaluation of a novel anthraquinone compound (1,8-dihydroxy-6-methyl-9,10-anthraquinone-3-oxy ethyl succinate) named Kanglexin (KLX), as a potent cardioprotective agent with antifibrosis activity. Our results demonstrated that the administration of KLX by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In non-canonical responses, three pathways (PI3K/Akt, RhoA-ROCK axis, and MAPK cascades) can be directly activated by TGF-β [ 33 ]. A few studies reported that TGF-β1 regulated cardiac fibrosis through the activation of the non-canonical responses [ 76 ]. Tao et al demonstrated that miRNA-29a could act as a key regulator to suppress the proliferation of cardiac fibroblasts by targeting the VEGF-A/MAPK signaling pathway [ 41 ].…”
Section: The Functions Of Mirnas In Cardiac Fibrosis-related Signalin...mentioning
confidence: 99%
“…In non-canonical responses, three pathways (PI3K/Akt, RhoA-ROCK axis, and MAPK cascades) can be directly activated by TGF-β [ 33 ]. A few studies reported that TGF-β1 regulated cardiac fibrosis through the activation of the non-canonical responses [ 76 ]. Tao et al demonstrated that miRNA-29a could act as a key regulator to suppress the proliferation of cardiac fibroblasts by targeting the VEGF-A/MAPK signaling pathway [ 41 ].…”
Section: The Functions Of Mirnas In Cardiac Fibrosis-related Signalin...mentioning
confidence: 99%
“…Kanglexin, a synthetic anthraquinone, was found to possess higher biological activity and solubility but lower toxicity than natural anthraquinone compounds [ 169 ]. Kanglexin reportedly affords various cardiovascular benefits, such as preventing myocardial injury and cardiac insufficiency after myocardial infarction through the NLRP3 pathway [ 170 ]; inhibiting myocardial fibrosis and cardiac remodelling through TGF-β1/ERK1/2 noncanonical pathway [ 171 ]; and reversing myocardial senescence by binding to the ubiquitin-like domain of Parkin, a key regulatory protein of mitochondrial autophagy [ 169 ]. A recent study revealed that kanglexin promoted angiogenesis and wound healing by stimulating the FGFR1/ERK signalling pathway, indicating potential therapeutic effects in diabetic foot syndrome [ 172 ].…”
Section: Effects Of Antidiabetic Drugs On Pcsk9mentioning
confidence: 99%